High‐temporospatial‐resolution dynamic contrast‐enhanced (DCE) wrist MRI with variable‐density pseudo‐random circular Cartesian undersampling (CIRCUS) acquisition: evaluation of perfusion in rheumatoid arthritis patients. (26th November 2015) - Liu, Jing; Pedoia, Valentina; Heilmeier, Ursula; Ku, Eric; Su, Favian; Khanna, Sameer; Imboden, John; Graf, Jonathan; Link, Thomas; Li, Xiaojuan
Abstract : This study is to evaluate highly accelerated three‐dimensional (3D) dynamic contrast‐enhanced (DCE) wrist MRI for assessment of perfusion in rheumatoid arthritis (RA) patients. A pseudo‐random variable‐density undersampling strategy, circular Cartesian undersampling (CIRCUS), was combined with k–t SPARSE‐SENSE reconstruction to achieve a highly accelerated 3D DCE wrist MRI. Two healthy volunteers and 10 RA patients were studied. Two patients were on methotrexate (MTX) only (Group I) and the other eight were treated with a combination therapy of MTX and anti‐tumor necrosis factor (TNF) therapy (Group II). Patients were scanned at baseline and 3 month follow‐up. DCE MR images were used to evaluate perfusion in synovitis and bone marrow edema pattern in the RA wrist joints. A series of perfusion parameters was derived and compared with clinical disease activity scores of 28 joints (DAS28). 3D DCE wrist MR images were obtained with a spatial resolution of 0.3 × 0.3 × 1.5 mm 3 and temporal resolution of 5 s (with an acceleration factor of 20). The derived perfusion parameters, most notably transition time (d T ) of synovitis, showed significant negative correlations with DAS28‐ESR ( r = −0.80, p < 0.05) and DAS28‐CRP ( r = −0.87, p < 0.05) at baseline and also correlated significantly with treatment responses evaluated by clinical score changes between baseline and 3 month follow‐up (with DAS28‐ESR r = −0.79, p < 0.05, and DAS28‐CRP r = −0.82, p < 0.05). Highly accelerated 3D DCE wrist MRI with improved temporospatial resolution has been achieved in RA patients and provides accurate assessment of neovascularization and perfusion in RA joints, showing promise as a potential tool for evaluating treatment responses. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : High temporospatial resolution 3D DCE wrist MRI has been achieved in RA patients with a data acquisition acceleration factor of 20, which provides accurate quantitative assessment of neovascularization and perfusion in RA joints. Such a technique improved monitoring of treatment response and disease progression, and thus has great potential to allow early detection of RA and help with optimizing treatment strategy for patients with RA.